The qualitative study of intentional self-harm in Thailand: Focusing on predisposing child-rearing environments and self-harm cessation - Limsuwan, Nida; Lantomrattana, Anyamanee; Prachason, Thanavadee; Tantrarungroj, Thanita; Lorterapong, Passaporn; Thongpan, Masatha; Waleeprakhon, Punjaporn (Frontiers in Psychology, 2023)
Intentional self-harm in adolescents and young people included both suicidal behaviors and nonsuicidal self-injury (NSSI) is a serious issue in mental health systems. However, the majority of studies on self-harm in adolescents and young people focused on quantitative methodology which might has limitations to explain this complex phenomenon of intentional self-harm. Therefore, this study aimed to describe the subjective experiences of adolescents and young people who presented with intentional self-harm in order to provide better understanding of this behavioral phenomenon. This is an exploratory qualitative study used phenomenological processes and thematic analysis. Twenty subjects aged 13-29 years were included in this study. The results revealed 6 themes regarding predisposing child - rearing environments and 9 themes regarding factors related to cessation of intentional self-harm. Moreover, it demonstrated the important functions of self-harm as an intrapersonal strategy for emotional regulation. In conclusion, this study underscored the importance to understand the developmental pathways as well as the cessation pathways of these complex behaviors.